Sensitive Electrochemical Determination of Luteolin in Chrysanthemum morifolium Ramat Using a Copper Nanocluster/Graphene-Modified Electrode - Yang, Tiejin; Jiang, Du (Asian Journal of Chemistry, 2013)
A simple and highly sensitive electrochemical method was developed for the determination of trace-level luteolin, based on the copper nanocluster/graphene-modified electrode. Scanning electron microscopy were used for the characterization of the distribution of the copper nanoclusters on the graphene matrix. The composite of the copper nanocluster/graphene was investigated by the electrochemical characterization of cyclic voltammetry and electrochemical impedance spectroscopy. The preliminary study shows that the sensor has synergistic electrocatalytic activity to the oxidation of luteolin. The linear range for the detection of the luteolin is 7.0 × 10-7-3 × 10-6 M, a low detection limit of 3 × 10-8 M. Experiment results also showed that the sensor has good reproducibility and is interference free. The analytical performance of this sensor has been evaluated for detection of luteolin in Chrysanthemum morifolium Ramat as a real sample.